Corrosively of peroxide solutions against conventional and electro less NI-P-CNF/ (tio2-zro2) Nano coatings materials - Kumar Dhiman, Manoj; Kumar, Manoj; Ram, Munna; Sharma, Sulaxna; Sharma, Awanish (International Journal of Engineering and Technology, 2018)
In the present experimental effort, an electroless Ni-P-CNF and the Ni-P-TiO2-ZrO2 nano-composite coatings have been deposited on basic mild steel (grade AISI1400) substrate. For EL Ni-P-CNF coating an amount (5 gpl) of activated CNF nano-particles and for Ni-P-TiO2-ZrO2 a mixture of equal amount (2.5 gpl each) of TiO2/ZrO2 nano-particles were incorporated into an acidic electroless Ni-P bath as a second phase material and were reduced by a reducing agent named sodium hypophosphite. After electroless coating, as-prepared Ni-P-CNF and Ni-P-TiO2-ZrO2 EL depositions were heated at 400 ï¯C in Ar environment for one hour duration and were analysed for surface morphology and elemental composition by FESEM and EDAX methods. A compact, homogeneous and consistent allocation of CNF nano-particles and uniform allocation of TiO2+ZrO2 nano-particles into EL Ni-P matrixes is observed respectively, through results analyses of FESEM and EDAX methods. The long term immersion weight loss corrosion test results in alkaline peroxide solutions anticipated that electroless nano-composite coatings demonstrate better corrosion resistance as against to MS, SS316L conventional steels and analogous to duplex stainless steel 2205. Further, the enhanced peroxide and chloride containing solutions are more corrosive than less peroxide and without chloride solutions.Â